2021
DOI: 10.3389/fonc.2021.719355
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Prognostic Model Based on 2-Gene Signature and Analysis of Corresponding Tumor Microenvironment in Alcohol-Related Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most prevalent malignant tumors with the poor prognosis. Nowadays, alcohol is becoming a leading risk factor of HCC in many countries. In our study, we obtained the DEGs in alcohol-related HCC through two databases (TCGA and GEO). Subsequently, we performed enrichment analyses (GO and KEGG), constructed the PPI network and screened the 53 hub genes by Cytoscape. Two genes (BUB1B and CENPF) from hub genes was screened by LASSO and Cox regression analyses to construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(53 reference statements)
0
1
0
Order By: Relevance
“… 34 The percentages of immune cell types infiltrating the tumor immune microenvironment can significantly influence the malignant biological behavior of tumors. Other members of the centromere protein family (CENPF 35 , 36 and CENPM 31 ) are also associated with infiltration of multiple immune cell types in HCC. GO analysis demonstrated that the main biological processes involving CENPO include humoral immune responses and complement activation.…”
Section: Discussionmentioning
confidence: 99%
“… 34 The percentages of immune cell types infiltrating the tumor immune microenvironment can significantly influence the malignant biological behavior of tumors. Other members of the centromere protein family (CENPF 35 , 36 and CENPM 31 ) are also associated with infiltration of multiple immune cell types in HCC. GO analysis demonstrated that the main biological processes involving CENPO include humoral immune responses and complement activation.…”
Section: Discussionmentioning
confidence: 99%